Short report on cases of several head injuries - Shah, Vijay A; Nira Gaonkar; Nilima Karnik (Journal of All India Institute of Speech and Hearing, 1972)
During the period of past two years, two cases were seen in the Speech and Hearing Centre, Sir J J . Group of Hospitals, with the complaint of severe loss of hearing in both the ears.